THE INFLUENCE OF THE BIOLOGICAL ACTIVATOR NUTRILIFE ON THE YIELD AND QUALITY OF ONIONS - Rosa, R.; Franczuk, J.; Zaniewicz-Bajkowska А.; Remiszewski, K.; Dydiv, O.; Andrejiová, A (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Belonging to the Alliaceae family, onion (Allium cepa L.) is one of the most important and popular vegetable and spice crops grown all over the world. Onions are demanding on soil fertility. It is especially demanding to the increased concentration of mineral salts in the soil. At the beginning of the growing season, onion plants must be supplied with nitrogen. A high yield of onions is obtained on light fertile sandy and loamy soils with a pH of 6-7. Correct provision of plants with macro- and microelements can have a beneficial effect on the growth and yield of turnip onions, which is extremely important on poor soils. At the time when environmental protection is becoming an important concern, new friendly methods of stimulating plant growth are being investigated, among others, by applying macroelements, microelements and various growth stimulants to the leaves. One of the new products is Nutrilife, a biological activator. It is a combination of macro- and microelements (EDTA), humic and fulvic acids, enzymes and amino acids. The field experiment was carried out in east-central Poland, 85 km east of Warsaw, on Luvisol soil. The aim of the studies was to determine the effect of Nutrilife applied to leaves during the BBCH 19 stage, with the simultaneous reduction of nitrogen or phosphorus soil doses by half, on the yield and the content of dry matter and sugars in onion. The Nutrilife activator allowed half reducing mineral nitrogen or phosphorus doses, while the yield was the same as in the case of full NPK treatment. The effect of Nutrilife on onion dry matter content was dependent on the weather conditions in the years of research and the applied mineral fertilizer treatment. There was no significant effect of the activator on the total sugar content.